Technology in Education: The Use of Relevant Instructional Technologies to ImproveTeaching and Learning English as a Foreign Language: The Case of Sumaiyah Preparatory School in Anbar Province - Habeeb , Mohammed Hussein; Elttayef Al-Abdali , Ahmed Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
The modern application of technology represents an important evidence in contemporary English language teaching methods. Instructional technologies provided the educational system with unlimited various tools and options that enabled learners and teachers in the process of language development (Al-Abdali, 2016). Contemporary English language teachers should incorporate different kinds of technological aids to facilitate the delivery of knowledge. The current study tried to address different types of technology which should be utilized in English language teaching classrooms. For the purposes of this study, the relevant literature has been reviewed. In light of this, the researcher outlines the fundamental research problem, elucidates the significance of the research objectives, and presents the findings. The paper concludes by offering a number of recommendations which may further contribute to the improvement of teaching methods by advancing the widespread application of modern technology.